# 3r+6st+5r+3st-7st=

## Simple and best practice solution for 3r+6st+5r+3st-7st= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3r+6st+5r+3st-7st= equation:

Simplifying
3r + 6st + 5r + 3st + -7st = 0

Reorder the terms:
3r + 5r + 6st + 3st + -7st = 0

Combine like terms: 3r + 5r = 8r
8r + 6st + 3st + -7st = 0

Combine like terms: 6st + 3st = 9st
8r + 9st + -7st = 0

Combine like terms: 9st + -7st = 2st
8r + 2st = 0

Solving
8r + 2st = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-2st' to each side of the equation.
8r + 2st + -2st = 0 + -2st

Combine like terms: 2st + -2st = 0
8r + 0 = 0 + -2st
8r = 0 + -2st
Remove the zero:
8r = -2st

Divide each side by '8'.
r = -0.25st

Simplifying
r = -0.25st